Travestilidade, o feminino como falo - Oliveira, Christiana Paiva de (2016)
This dissertation, written under the influence of Fundamental Psychopathology, addresses questions referring to Tranvestility and elements related to this manifestation. The title was born from a set of clinical care attendances - made by a NGO that cares for GLSBT people – where one of the patients speaks uninterruptedly about his mother. In these moments, the patient mentions a will to transvest that would not exist if it wasn’t for the influence of the mother; he constantly denies the analyst’s speech about it and any other who approaches the established dynamics between his mother and him – seen as perfect, although she was awfully sick. The risen hypothesis is that excessive denial, as well as the emphasis on the mother figure, connects to his will to transvest. In distinction to this case study, this essay intends to emphasize the mother figure as one of the instances of the feminine to the child, inferring to the thought of transvestility having an identification with femininity. For all, questions about narcissism, Oedipus complex and castration gain prominence inside the research and combine to the mechanism of denial. His issues on caring and on body entwine, bringing along considerations towards eroticism, present on the mother-son relation and modifications on the patient’s body. On the presented relationship, transvest hismself would be having access to an idealized body through erotization while providing live to an almost-dead mother